Alleviating heat stress on broiler breeder hens: Effect of dietary antioxidant supplementation on reproductive performance, egg quality, offspring growth, and antioxidant capacity - Phocharapon Pasri; Chayanan Pukkung; Pascal Mermillod; Nadine Gérard; Orapin Jantasaeng; Merisa Sirisopapong; Supattra Okrathok; Thanatat Thiabching; Sitthipong Rakngam; Kanokwan Kamkajon; Yongcai Zhu; Sutisa Khempaka (Journal of Applied Poultry Research)
SUMMARY: The purpose of this study was to investigate the effects of antioxidant compounds derived from synthetic sources (a combination of 200 mg vitamin C/kg, 150 mg vitamin E/kg, 0.30 mg Se yeast/kg, and 150 mg carnitine/kg) and phytogenic sources (a 1 % combination of clove, green tea pomace, and Vietnamese coriander) in breeder hens under heat stress (HS) on reproductive performance, egg quality, and offspring growth performance, and their antioxidant capacity. One hundred breeder hens were randomly divided into four treatments to receive either a basal diet or a basal diet supplemented with synthetic or phytogenic antioxidants under thermoneutral (TN) (23 ± 1 °C) and chronic HS (36 ± 1 °C for 4 h/day) conditions: T1: TN + basal diet, T2: HS + basal diet, T3: HS + synthetic antioxidants, and T4: HS + phytogenic antioxidants. The results showed that either synthetic or phytogenic antioxidants can improve the Haugh unit and maintain ovary weight, and large and small yellow follicles (P < 0.05). In addition, phytogenic antioxidants were also found to enhance egg yolk color. Although the body weight of offspring from either antioxidant source was initially low on day 1, it subsequently increased until reaching levels comparable to those in the TN and HS without supplementation by 3 weeks of age (P > 0.05). Either antioxidant source can improve free radical scavenging, reduce lipid peroxidation, upregulate the relative expression of SOD, CAT, and GSH-Px mRNA, and downregulate HSP90 in offspring liver (P < 0.05). This study highlights the beneficial effects of combining either synthetic or phytogenic antioxidants to mitigate the negative impact of HS on breeder hens and the maternal antioxidant properties transmitted to their offspring.